Gene editing in the nematode parasite Nippostrongylus brasiliensis using extracellular vesicles to deliver active Cas9/guide RNA complexes - Hagen, Jana; Ghosh, Subhanita; Sarkies, Peter; Selkirk, Murray E. (Frontiers in Parasitology, 2023)
Despite recent advances, animal-parasitic nematodes have thus far been largely refractory to genetic manipulation. We describe here a new approach providing proof of principle that CRISPR/Cas9-mediated gene editing of parasitic nematodes is achievable using vesicular stomatitis virus glycoprotein-pseudotyped extracellular vesicles for the delivery of Cas9-single guide ribonucleoprotein complexes. We demonstrate that extracellular vesicle-delivered ribonucleoproteins can be used to disrupt a secreted deoxyribonuclease in Nippostrogylus brasiliensis. Introduction of a repair template encoding multiple stop codons led to measurable reduction in expression of the targeted gene. Altered transcripts corresponding to the edited locus were detected by RT-PCR, demonstrating that vesicles can access cells of tissues actively expressing the gene of interest. These data provide evidence that this technique can be employed for targeted gene editing in N. brasiliensis, making this species genetically tractable for the first time, although further refinement will be necessary for routine and robust interrogation of gene function.